A Study on Coupling Faults’ Characteristics of Fixed-Axis Gear Crack and Planetary Gear Wear - Xin Wang (Shock and Vibration)
To identify the fault frequency characteristics of the gear transmission system under coupling fault of fixed-axis gear crack and planetary gear wear, dimensionless dynamical equations of gear transmission system were established. Bifurcations in normal condition and coupling fault condition were contrasted. The affected excitation frequency range was found. Fault frequency characteristics in sensitive interval caused by the coupling fault of fixed-axis gear crack and planetary gear wear were analyzed. Simulation analysis shows that the crack fault in fixed-axis gear brings up peaks in doubling of 1~10 for fault frequency, the wear fault in planetary gear increases the amplitude of meshing frequency and its double and triple, and the coupling of both shows two kinds of fault features around the planetary gear meshing frequency.